PERENCANAAN KEBUTUHAN ALAT BERAT PROYEK REKLAMASI PELABUHAN SORONG - Johanes Asdhi P., Diki Firmansah, Marjono, (Prokons: Jurnal Teknik Sipil, 2018)
One disadvantages of Sorong Port is not able to accommodate the incoming vessels, as the container port has been united with the passenger port. Therefore, the northern coast is to be reclaimed to provide more port area. To make this 50,000-m² reclamation project run smoothly, the use of heavy equipment must be appropriate in terms of type, size, quantity, and site situation. The purpose of thesis is to find out the type of heavy equipment needed, the number of equipment needs, and the cost of heavy equipment. The required secondary data of Sorong shop drawings, work specifications, material and work unit price of Sorong 2016 and heavy equipment specifications. The planning comprised embankment and reclamation works.The planning results of heavy equipment comprising 1 units of excavator on 39 work weeks, 1 units of excavator long boom on 5 work weeks, 70 units of dump truck on 39 work weeks, 1 units of motor grader on 13 work weeks, 1 units of wheel loader on 10 work weeks, and 1 units of vibrator roller on 11 work weeks; at a total cost of IDR 56,343,100,000.00 Keywords: reclamation, productivity, heavy equipment